Serum Chemokine-release Profiles in AML-patients Might Contribute to Predict the Clinical Course of the Disease. (18th May 2020) - Merle, M.; Fischbacher, D.; Liepert, A.; Grabrucker, C.; Kroell, T.; Kremser, A.; Dreyssig, J.; Freudenreich, M.; Schuster, F.; Borkhardt, A.; Kraemer, D.; Koehne, C.-H.; et al.
ABSTRACT: In cancer or hematologic disorders, chemokines act as growth- or survival factors, regulating hematopoiesis and angiogenesis, determining metastatic spread and controlling leukocyte infiltration into tumors to inhibit antitumor immune responses. The aim was to quantify the release of CXCL8, −9, −10, CCL2, −5, and IL-12 in AML/MDS-pts' serum by cytometric bead array and to correlate data with clinical subtypes and courses. Minimal differences in serum-levels subdivided into various groups (e.g. age groups, FAB-types, blast-proportions, cytogenetic-risk-groups) were seen, but higher release of CXCL8, −9, −10 and lower release of CCL2 and −5 tendentially correlated with more favorable subtypes (<50 years of age, <80% blasts in PB). Comparing different stages of the disease higher CCL5-release in persisting disease and a significantly higher CCL2-release at relapse were found compared to first diagnosis – pointing to a change of 'disease activity' on a chemokine level. Correlations with later on achieved response to immunotherapy and occurrence of GVHD were seen: Higher values of CXCL8, −9, −10 and CCL2 and lower CCL5-values correlated with achieved response to immunotherapy. Predictive cut-off-values were evaluated separating the groups in 'responders' and 'non-responders'. Higher levels of CCL2 and −5 but lower levels of CXCL8, −9, −10 correlated with occurrence of GVHD. We conclude, that in AML-pts' serum higher values of CXCL8, −9, −10 and lower values of CCL5 and in part of CCL2 correlate with more favorable subtypes and improved antitumor'-reactive function. This knowledge can contribute to develop immune-modifying strategies that promote antileukemic adaptive immune responses.